Effects of herpes zoster vaccination and antiviral treatment on the risk of stroke: a systematic review and meta-analysis - Jia, Yong-hui; Dong, Yu-bo; Jiang, Hai-yin; Li, Ai-juan (Frontiers in Neurology, 2023)
Background Evidence suggests that there is an increased risk of stroke after herpes zoster (HZ). However, reports on the effects of HZ vaccination (HZV) and antiviral treatment on stroke risk are inconsistent. Thus, we examined these associations in a meta-analysis. Methods To identify relevant studies, we searched three databases for articles published up to January 2023. Random-effect models were examined to determine overall pooled estimates and 95% confidence intervals (CIs). Results This review included 12 observational studies (six on HZV and seven on antiviral treatment). When comparing vaccinated and unvaccinated patients, vaccination was found to be associated with a lower risk of stroke (OR, 0.78; 95% CI 0.68–0.9; P = 0.001). A meta-analysis of self-controlled case series (SCCS) revealed evidence of a reduced OR in individuals who received the vaccine (OR, 1.14; 95% CI 0.94–1.37; P = 0.181) compared with unvaccinated individuals (OR, 1.36; 95% CI 1.15–1.61; P < 0.001). Compared with untreated patients, antiviral therapy was not associated with a reduced risk of stroke (OR, 1.13; 95% CI 0.94–1.36; P = 0.201). The meta-analysis of the SCCS showed no evidence of a reduced OR in individuals who received antiviral therapy (OR, 1.33; 95% CI 1.17–1.51; P < 0.001) compared to untreated individuals (OR, 1.45; 95% CI 1.25–1.69; P < 0.001). Conclusions This meta-analysis suggests that the HZV, but not antiviral treatment, decreases the odds of developing stroke.